Clinical profiles of Chinese patients with diffuse panbronchiolitis - Tsang, Kenneth W T; Ooi, Clara G C; Ip, Mary S M; Lam, Wah-kit; Ngan, Henry; Chan, Eric Y T; Hawkins, Brian; Ho, Chu-shak; Amitani, Ryoichi; Tanaka, Eisaku; Itoh, Harumi (Thorax, 1998)
BACKGROUND Diffuse panbronchiolitis (DPB), characterised by progressive sinobronchial sepsis, is well characterised in Japanese subjects but not in other ethnic groups. The experience with DPB in seven Chinese patients is described and the clinical profiles compared with those of Japanese subjects. METHODS Seven Chinese patients (three women; mean (SD) age 48(18.6) years, all never smokers) who attended a teaching hospital centre and fulfilled the diagnostic criteria for DPB were assessed prospectively for clinical, radiological, lung function, microbiological, and other “characteristic” laboratory parameters. RESULTS Lung function assessment showed a typical obstructive pattern (n = 5) and air trapping (n = 7). Typical bronchiolar infiltration by lymphocytes and plasma cells and accumulation of foamy macrophages in the intraluminal tissue were detected in open lung biopsy specimens (n = 2). Chest radiographs and high resolution computed tomographic scans revealed hyperinflation, diffuse nodules, bronchial thickening and dilatation, peripheral hypoattenuation, and bronchiolectasis. Radiological improvement, manifest as a reduction in nodular density and bronchial thickening, and persistence of other abnormalities such as air trapping were not accurately depicted by the classical Nakata or Akira classifications. The other “characteristic” features such as HLA-B54, IgG subclass deficiency, raised CD4/CD8 T lymphocyte ratio, cold haemagglutinaemia, raised IgA, IgG, and rheumatoid factor were not present. Treatment with erythromycin led to excellent responses in symptoms, lung function indices, and the radiological picture. A review of the non-Japanese cases in the literature reveals that this absence of typical “additional features” in DPB might also be applicable to non-Japanese patients. CONCLUSIONS We report the only series of non-Japanese Mongoloid patients with well characterised DPB who had uncharacteristic investigation profiles. This experience should help other clinicians in the investigation and management of DPB in non-Japanese patients.